Influence of FMO3 and CYP3A4 Polymorphisms on the Pharmacokinetics of Teneligliptin in Humans - Park, Jin-Woo; Kim, Kyoung-Ah; Kim, Jong-Min; Park, In-Hwan; Park, Ji-Young (Frontiers in Pharmacology, 2021)
Teneligliptin, a dipeptidyl peptidase-4 inhibitor, is used to treat type 2 diabetes mellitus. FMO3 and CYP3A4 metabolize teneligliptin into teneligliptin sulfoxide. This study examined the effects of FMO3 (rs909530, rs1800822, rs2266780, and rs2266782) and CYP3A4 (rs2242480) polymorphisms on teneligliptin pharmacokinetics at a steady state among 23 healthy participants administered 20 mg teneligliptin daily for 6 days. Subjects with FMO3 rs909530, rs2266780, and rs2266782 polymorphisms exhibited a significant gene dosage-dependent increase in maximum steady-state plasma drug concentration (Cmax,ss) and area under the drug concentration vs. time curve (AUC) (p<0.05). However, the Cmax values significantly decreased but the AUC values did not significantly vary in subjects with CYP3A4 polymorphism (rs2242480). These results suggest that FMO3 and CYP3A4 polymorphisms affect teneligliptin pharmacokinetics in humans. The findings of this study provide a scientific basis for the inter-individual variation in teneligliptin disposition.